Pengaruh Implementasi Building Information Modeling (BIM) terhadap Efisiensi Perencanaan dan Pelaksanaan Proyek Konstruksi pada Program Studi Teknik Sipil - Ajinar (Jurnal Humaniora Pendidikan (JHP), 2026)
The rapid development of digital technology in the construction industry has increased the need for more effective and efficient project management systems. One of the technologies currently widely implemented in the construction sector is Building Information Modeling (BIM), a digital-based modeling method capable of integrating all project information into a single system. This study aims to analyze the effect of BIM implementation on the efficiency of planning and execution of construction projects in Indonesia's civil engineering sector. The research employed a quantitative approach using an explanatory survey method. The study population consisted of construction professionals experienced in BIM implementation, while purposive sampling was used to select 150 respondents from contractors, consultants, supervisors, and government agencies. Data were collected using a five-point Likert scale questionnaire and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS 4 software. The results revealed that BIM implementation had a positive and significant effect on construction project efficiency, with a path coefficient value of 0.827, a t-statistic value of 18.546, and a p-value of 0.000. The coefficient of determination (R²) of 0.684 indicates that BIM implementation explains 68.4% of the variance in project efficiency. BIM implementation was proven to improve stakeholder coordination, reduce rework, increase cost estimation accuracy, and enhance project schedule control. Therefore, BIM implementation should continue to be strengthened through improving human resource competencies, government policy support, and integrating BIM education into civil engineering curricula to support the digital transformation of Indonesia's construction industry